2020
DOI: 10.3390/cryst10080675
|View full text |Cite
|
Sign up to set email alerts
|

Orientation Control of Helical Nanofilament Phase and Its Chiroptical Applications

Abstract: Chiral liquid crystal phases show fascinating structural and optical properties due to their inherent helical characteristics. Among the various chiral liquid crystal phases, the helical nanofilament phase, made of achiral bent-shaped molecules, has been of keen research interest due to its unusual polar and chiral properties. This review is intended to introduce the recent progress in orientation control and its application to the helical nanofilament phase, which includes topographic confinement, photoalignm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 106 publications
0
15
0
Order By: Relevance
“…[ 49 ] To unequivocally determine the mesoscopic morphology of the dark conglomerate phase, transmission electron microscopy (TEM) was used. TEM images of a dropcasted and heat‐annealed (i.e., heated above the isotropization point and then cooled down back to room temperature at 20 K min −1 ) material revealed helical nanofibers with dimensions characteristic of LC HNFs: [ 50–53 ] Pitch p ≈ 230 nm, width w ≈ 45 nm, thickness z ≈ 15 nm (Figure 1c). OIM nanofibers formed dendritic domains, suggesting that fibers in a single domain grow from a single nucleation point upon freezing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 49 ] To unequivocally determine the mesoscopic morphology of the dark conglomerate phase, transmission electron microscopy (TEM) was used. TEM images of a dropcasted and heat‐annealed (i.e., heated above the isotropization point and then cooled down back to room temperature at 20 K min −1 ) material revealed helical nanofibers with dimensions characteristic of LC HNFs: [ 50–53 ] Pitch p ≈ 230 nm, width w ≈ 45 nm, thickness z ≈ 15 nm (Figure 1c). OIM nanofibers formed dendritic domains, suggesting that fibers in a single domain grow from a single nucleation point upon freezing.…”
Section: Resultsmentioning
confidence: 99%
“…In the context of achieving higher g‐values in the visible range, the performed optical modelling directs our attention toward optimizing the characteristic of constituents to increase length of the helical assemblies (Figure 4g) and achieving directional control over HNF growth [ 77 ] (Figures S37 and S38, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…An HNF is formed by twisted smectic layers composed of BLC molecules (Figure 1). [15, 26, 27] Here, a dimeric molecule having aromatic groups on both sides of a central alkyl linkage with an odd number of C atoms (Figure 1 a) was used as BLC [19, 28, 29] . In particular, it was reported that D–n dimers with photoresponsive azobenzene moieties in their arm parts could be uniaxially oriented when irradiated with unpolarized UV light due to the Weigert effect [19] .…”
Section: Resultsmentioning
confidence: 99%
“…The absence of residual solvent in the sample was examined via phase-transition temperature measurement using polarized optical microscopy (POM). In the mixture system, unique phases found in the BC molecule, such as B2 and B7, readily disappeared upon mixing of the rod-like mesogen [8,13,14]. Instead, the aforementioned nano-sized separation phases, such as <HNF/N>, <HNF/SmA>, and <HNF/Iso> were observed.…”
Section: Methodsmentioning
confidence: 98%
“…A mixed system, consisting of an achiral bent-core (BC) molecule and rod-like nematogen, has been reported as a promising chiroptic material [4][5][6][7][8]. In this system, nano-sized phase separation-between helical nanofilaments (HNF) originating from the BC molecule and the calamitic liquid-crystalline (LC) nematic (N) phase originating from rod-like nematogen-shows high chiropticity, such as optical rotatory power or circular dichroism [5,9,10].…”
Section: Introductionmentioning
confidence: 99%